2021
DOI: 10.1002/adhm.202002048
|View full text |Cite
|
Sign up to set email alerts
|

You Talking to Me? Cadherin and Integrin Crosstalk in Biomaterial Design

Abstract: While much work has been done in the design of biomaterials to control integrin‐mediated adhesion, less emphasis has been put on functionalization of materials with cadherin ligands. Yet, cell–cell contacts in combination with cell–matrix interactions are key in driving embryonic development, collective cell migration, epithelial to mesenchymal transition, and cancer metastatic processes, among others. This review focuses on the incorporation of both cadherin and integrin ligands in biomaterial design, to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 200 publications
(217 reference statements)
0
30
0
Order By: Relevance
“…To properly design and develop functional and responsive biomaterials that successfully interact with tissue components, a deeper understanding of the behavior of cells at the biomaterial interface is very important. 21,22 It is widely known that integrin receptors, a family of cell surface adhesion receptors, play a key role in cell–biomaterial interaction and cell mechanotransduction. 22–25 The physical ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To properly design and develop functional and responsive biomaterials that successfully interact with tissue components, a deeper understanding of the behavior of cells at the biomaterial interface is very important. 21,22 It is widely known that integrin receptors, a family of cell surface adhesion receptors, play a key role in cell–biomaterial interaction and cell mechanotransduction. 22–25 The physical ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cadherins are linked to the cytoskeleton via β-catenin-αcatenin-actin complex, with an integrin-cadherin adhesive crosstalk taking place. 85 Studies in which MNPs have been used to target cadherins have revealed important information; for instance it has been described that the magnetic force Please do not adjust margins Please do not adjust margins application promotes the recruitment of F-actin and vinculin to the cadherin-MNP clusters, stabilizing the cadherin-cytoskeletal complexes (Figure 5). 8,86 In addition to VE-and E-cadherins, the same group investigated the cell surface activation of another classical mechanoreceptor, Notch1, whose activation promotes downstream signalling.…”
Section: Cellular Targets For Magnetogeneticsmentioning
confidence: 99%
“…Furthermore, cadherins are linked to the cytoskeleton via β-catenin-α-catenin-actin complex, with an integrin-cadherin adhesive crosstalk taking place. 85 Studies in which MNPs have been used to target cadherins have revealed important information; for instance, it has been described that the magnetic force application promotes the recruitment of F-actin and vinculin to the cadherin-MNP clusters, stabilizing the cadherin-cytoskeletal complexes (Fig. 5).…”
Section: Cellular Targets For Magnetogeneticsmentioning
confidence: 99%
“…Members of the cadherin transmembrane protein superfamily directly connect to actin and intermediate filaments in the cytoplasm and are extracellularly stabilized by Ca 2+ ions. These proteins interact with each other and extracellular matrix proteins and mediate cell clustering during development [ 8 ]. The presence of Ca 2+ ions in the hydrogel is therefore essential for cellular self-organization via cadherins.…”
Section: Bioinks As the Crucial Components For Cell Survival Differentiation And Structural Integritymentioning
confidence: 99%
“…The presence of Ca 2+ ions in the hydrogel is therefore essential for cellular self-organization via cadherins. The integrin receptor family controls cell–cell and cell–matrix interaction, binds to collagen (and the protease-digested derivative gelatin) and especially to a motive formed by the amino acids arginine, glycine and aspartate (RGD)-motive that is present in the extracellular matrix proteins fibronectin, vitronectin and laminin [ 8 ]. Therefore, either natural, protein ECM components that contain binding sites for membrane receptors must be included in the bioink, or synthetic/polysaccharide-based matrix components have to be functionalized with peptides such as RGD to allow adhesion, migration and to preserve viability.…”
Section: Bioinks As the Crucial Components For Cell Survival Differentiation And Structural Integritymentioning
confidence: 99%